Exploring climate-driven phenological mismatches in pears, pests and natural enemies: a multi-model approach - Laura A. Reeves; Tim Belien; Deepa Senapathi; Michael P. D. Garratt; Michelle T. Fountain (Journal of Pest Science, 2025)
Pear psyllid ( Cacopsylla pyri ) is the dominant pest of UK pear orchards, with an estimated cost of £5 million per annum. Insecticide withdrawal and increased pesticide resistance of C. pyri have led many growers to depend more on natural enemies for pest management, including earwigs. However, there is concern how phenological events may shift with future climate change, which may result in phenological mismatches. This study aimed to determine shifts in timing of phenological events within an agroecosystem and predict phenological mismatches or synchronies between trophic levels. We evaluated three models: the C. pyri phenology model, the earwig degree day model and the PhenoFlex model (flowering time). Phenological events predicted by models included: first, full and last flowering time for Pyrus communis ; peak psyllid abundance date for first-generation (G1) C. pyri nymphs and second-generation (G2) eggs, nymphs and adults; and peak abundance date for stage 4 Forficula auricularia and adults. Findings indicated that the timing of phenological events was advancing for all trophic levels, becoming significantly earlier under the current time period. Furthermore, predictions indicated that timing events would continue to advance under the RCP8.5 scenario. However, not all phenological events advanced at the same rate; the date of peak C. pyri G1 nymph abundance advanced at a higher rate than full flowering time, which could result in a phenological mismatch by 2071. Conversely, C. pyri and F. auricularia showed phenological synchrony, with peak abundance dates advancing at a similar rate, which could be beneficial for future biological control.